Synthesis and optimization of Novel Chitosan/Cellulose Acetate Natural Polymer Membrane for water treatment - Kamal, M.; Abdelrazek, E.M.; Sellow, N.M.; Abdelghany, A.M. (JOURNAL OF ADVANCES IN PHYSICS, 2018)
Chitosan (Ch) and Cellulose Acetate (CA) natural polymer in addition to other samples with different mass fractions of Chitosan/Cellulose Acetate (Ch/CA) were synthesized via simple casting route. Prepared samples were studied using FT-IR and UV/vis spectroscopic techniques. Structural variations due to the process of blending were retraced using X-ray diffraction data (XRD) and morphological investigation using scanning electron microscopy (SEM). Obtained spectral data reveals compatibility and complexation between polymer constituents identified through presence of polymer characteristic peaks with small variation in both intensity and position along with change in the value of optical energy gap from UV optical absorption spectral data. XRD pattern indicate the semicrystalline nature of the studied sample with an observable change in the crystallinity. Moreover, scanning electron microscopic (SEM) micrographs reveals homogenous structure without any evidence for agglomerations nearly in all compositions.